Mensagens sobre cuidados para mulheres no puerpério: contribuições para tecnologia cuidativo-educacional - SILVA, Polyana Cabral da (2024)
INTRODUCTION: The puerperium is a critical and fragile phase in a woman's life and some barriers make access to health services difficult. Rapid access to relevant and reliable information contributes positively to health outcomes, and the use of messaging applications can favor nursing care by facilitating the provision of necessary information, practical solutions, and biopsychosocial support in the postpartum period. OBJECTIVE: To develop messages, in the form of cards, about care for women in the postpartum period. METHODOLOGICAL APPROACH: This is a methodological study, carried out in three stages. The first stage consisted of an integrative literature review with the aim of identifying the care to be addressed in the postpartum care messages. The second stage, based on Freire's assumption of dialogicity, involved the preparation of text messages and cards, in the form of questions, based on the results obtained in the previous stage. The third stage consisted of validating the content and appearance of text messages and cards about care for women in the postpartum period. For content validation, the Health Education Content Validation Instrument was used, and for appearance validation, the Health Education Technology Appearance Validation Instrument was used, with items with a Content Validity Index (CVI) and Appearance Validity Index (IVA) > 0.78 being considered valid. The study was carried out from August 2023 to March 2024 and obtained a favorable ethical opinion under number 6.455.850. RESULTS: The literature review identified the main contents to be presented to women in the postpartum period: guidance on breastfeeding, assessment of lochia, care of the surgical wound and body hygiene, iron supplementation, physical activity, assistance related to postpartum depression, reproductive planning, guidance on sleep and rest, and labor rights. In this way, text messages and cards were created that addressed the identified content. The messages were organized in a table that showed the period for sending, content, content description and printscreens of the cards, and were later sent to content experts and visual communication/design experts for validation. The Global Content Validity Index was 0.87, while the Global Face Validity Index was 0.77. To complement the validation, the experts' suggestions were considered, such as the inclusion of messages about the puerperal woman's family routine and the creation of a standard design for the cards, thus a new version of the messages and cards was created, requiring a new round of validation. In the second round of validation, the Global Content Validity Index was 0.98; the Appearance Validity Index was 0.94, thus confirming the validity of the messages and high agreement among the experts. At the end of the study, 20 cards on care for women in the postpartum period were created and validated. CONCLUSION: The study enabled the development of text messages and cards about postpartum care, which will be used in a care-educational technology of the interaction group type in a messaging application, in which health professionals and postpartum women will participate. The messages were validated in terms of content and appearance, with high agreement between content experts and visual communication/design experts, and their use in an interaction group in a messaging application will enable interaction between professionals and postpKeywords: